Structure of Spatial Correlation Network and Influencing Factors of Urban-Rural Integration in China - Wang Kai; Liu Meilun; Tan Jiaxin; Gan Chang (Redai dili)
Urban-rural integration is a necessary way to realize the strategy of rural revitalization in the new era, and exploring the characteristics of the spatial correlation network of China's urban-rural integration and its formation mechanism is important for developing a comprehensive understanding of the spatial transmission mechanism of interregional urban-rural integration and provides a new policy perspective for the synergistic enhancement of the urban-rural integration level in each province. Based on China's interprovincial panel data from 2001 to 2021, the entropy method was applied to measure China's interprovincial urban-rural integration level, and the modified gravity model and social network analysis were used to explore the structural characteristics of China's spatial correlation network of urban-rural integration and its influencing factors. The results revealed the following: 1) During the study period, the level of China's interprovincial urban-rural integration showed an increasing trend, but the process of improvement was slow. Spatially, it showed a decreasing gradient from east to west, but the gap between the interprovincial urban-rural integration level gradually narrowed, with obvious spatial non-equilibrium. 2) China's urban-rural integration spatial association network became increasingly dense, complex, and close, and the main linkage flows of urban-rural integration occurred between geographically neighboring provinces and cities, such as Shanghai-Jiangsu, Shanghai-Zhejiang, and Beijing-Tianjin. The network connection was heterogeneous, and the network showed the characteristic of growth. However, the spatial connection of urban-rural integration did not reach the best level, and there is still much room for improvement. 3) Geospatial proximity, differences in the level of economic development, and urbanization had a significant positive effect on the optimization and evolution of the spatial linkage network of urban-rural integration, while differences in agricultural modernization and differences in advanced industrial structure showed a stage-by-stage effect over time. Differences in the scale of financial services did not have a significant effect. Accordingly, this study proposes countermeasures to optimize the spatial correlation network of urban-rural integration in China. Theoretically, it helps to deepen knowledge of the spatial effect and regional transmission of urban-rural integration in the geographical perspective. In practice, optimizing interprovincial urban-rural interaction and promoting cross-regional urban-rural integration development in a scientific and rational way are highly significant.